2014
DOI: 10.1038/hr.2014.44
|View full text |Cite
|
Sign up to set email alerts
|

Effects of exercise training on systo–diastolic ventricular dysfunction in patients with hypertension: an echocardiographic study with tissue velocity and strain imaging evaluation

Abstract: There is a lack of detailed data regarding the effect of exercise training in pharmacologically treated hypertensive patients. Therefore, the aim of this study was to evaluate the effects of exercise training on left and right ventricular morphologic and functional parameters by means of conventional echocardiography and sensitive new echocardiographic techniques including tissue Doppler velocity and strain imaging, that were performed in pharmacologically treated hypertensive patients at baseline and at the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 39 publications
1
15
0
Order By: Relevance
“…In the previous study to evaluate the effects of exercise training on systo-diastolic ventricular dysfunction in patients with HTN, strain and SR measurements demonstrated positive influence of exercise training, whereas conventional echocardiography revealed a mild degree of diastolic dysfunction without significant differences from baseline to the end of the exercise training protocol. 31 This finding suggested that strain and SR may detect more subtle change in diastolic function than conventional measurements. Although regional myocardial SR in the longitudinal direction during IVR derived from 2D-STE was shown to have a strong correlation with tau and to reflect LV relaxation, 10 global SR during IVR derived from previous 3D-STE has not been validated because of low volume rates.…”
Section: Discussionmentioning
confidence: 96%
“…In the previous study to evaluate the effects of exercise training on systo-diastolic ventricular dysfunction in patients with HTN, strain and SR measurements demonstrated positive influence of exercise training, whereas conventional echocardiography revealed a mild degree of diastolic dysfunction without significant differences from baseline to the end of the exercise training protocol. 31 This finding suggested that strain and SR may detect more subtle change in diastolic function than conventional measurements. Although regional myocardial SR in the longitudinal direction during IVR derived from 2D-STE was shown to have a strong correlation with tau and to reflect LV relaxation, 10 global SR during IVR derived from previous 3D-STE has not been validated because of low volume rates.…”
Section: Discussionmentioning
confidence: 96%
“…In humans, Leggio and colleagues observed in hypertensive patients that LV GLS significantly increased after training,24 while Hansen et al 25 found that a 3-month training programme was not able to alter LV GLS in overweight preadolescent children engaged in a competitive football season. Conversely, a previous study by Weiner et al ,9 investigating the impact of a 90-day period of training on LV twist mechanics in university male rowers, showed an increase in LV apical rotation, twisting and untwisting rate after training.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, lowering of blood pressure and prevention of hypertension is in first instance preferable by lifestyle changes, and many studies have shown the inverse association between physical activity level and the incidence of cardiovascular diseases suggesting low aerobic fitness as a strong predictor for future cardiovascular disease and all-cause mortality in both healthy and cardiovascular disease patients, including those with hypertension [2]. Although an important challenge is to increase the attention on strategies to maintain or improve fitness and to intensify and support the efforts to encourage physical activity, a large body of previous evidences demonstrated that an exaggerated blood pressure response to exercise is not an innocuous finding but associated with increased risk for cardiovascular events, and has been shown to be a predictor of future hypertension and risk of cardiovascular mortality [3].…”
mentioning
confidence: 99%
“…Although an important challenge is to increase the attention on strategies to maintain or improve fitness and to intensify and support the efforts to encourage physical activity, a large body of previous evidences demonstrated that an exaggerated blood pressure response to exercise is not an innocuous finding but associated with increased risk for cardiovascular events, and has been shown to be a predictor of future hypertension and risk of cardiovascular mortality [3]. Endothelial function, large artery stiffness and neurohormonal response are surely implicated both in the development of exaggerated blood pressure response to exercise and in the positive effect of physical exercise in the prevention and management of hypertension and cardiovascular disease in general; consequently, it seems mandatory to mutually promote early diagnosis/treatment of exaggerated blood pressure response to exercise in healthy subjects without hypertension and encourage physical activity in prevention, treatment, and control of all stages of hypertension [2, 4]. …”
mentioning
confidence: 99%